Changes in the growth rate during ontogenesis and methods of its investigation - Siniarska, Anna; Wolański, Napoleon (Studia Ecologiae et Bioethicae, 2005)
The problem of acceleration of growing processes during childhood and adolescence has been considered for a long time. The observations on this subject date back to the 19th century, however the attempts to summarize this phenomenon were dated to the 20th century. At the beginning of the 20th century Stratz, distinguishing the period of early and late childhood, had mentioned about three periods of deceleration and two periods of acceleration of growing processes. In 1930 also Boas identified the pubertal spurt. Ones of the first longitudinal studies had been organized in Krakow by Talko-Hryncewicz and continued in 1919-32. The results had been elaborated by Jasicki in 1934-48 and he revealed that there are two periods of acceleration of growing processes. In Poland this acceleration in growth had been called “the maximal height velocity.” The growth spurt at the end of childhood (around 7 years) has been pointed out by many authors in the 1930s, and in 1947 Tanner called it the mid-growth spurt. In 1961 Wolański pointed out that there are several growth spurts in childhood and called them pre (school) spurts. Consequently, in 1962 he had distinguished pubertal spurts for many somatic characteristics, and in 1964 – at least two pubertal spurts in height. Wolański had been analyzing the age at pubertal spurt followed by the age at menarche in rural and urban girls and concluded that these events are further apart if the pubertal spurt occurs later. The further analysis of these phenomena had been postponed because of the unfortunate statistical methods which presented data as mathematically smoothed growth curves and many details of individual growth patterns have been eliminated. Only two last decades the daily and monthly studies of growth processes have returned to favor, and the relationship between the rate and age at prepubertal and pubertal spurts has been studied again. In about 1980 the growth spurt at the turn of childhood and juvenile periods was again under study, but only during the last decade several growth spurts have been manifested. The number of prepubertal growth spurts has a very important impact on age and velocity of the pubertal spurt. If the number of prepubertal spurs is grater, the pubertal spurt occurs later and is less manifested. There are still many controversies according to the age of pubertal spurt and final body height. It may be similar to the relationship between menarche and final body height. It is observed that between populations there is a negative correlation between age at menarche and adult height, whereas between women within the population this correlation is positive (Wolański 1979).